RITUAL KEAGAMAAN MASYARAKAT DAYAK HINDU-BUDHA BUMI SEGANDU INDRAMAYU - I Putu Gede Ardhi Gunawan (Jurnal Pelita Dharma, 2014)
Dayak's  tribe is which as we know inltabit ttie island  of Borneo, but there arecommunities called themselves Hiruiu-Buddhis!   Dayak Bumi Segandu which is located i11Krimun Vilagge,  Losarang,  lndramayu  district.  Although if is almost similar  to  tirepattern of lifeof the Dayak tribe i11 Borneo in ways that are still traditional,  but  there are interesting things associated  with  religious rituals   iu   this comm1111ity   that adopts Kejawen because this  identity is 1101  affiliated  with any religion wlw haue legitimate recognized in tire  State of Indonesia.  There are two main ritual which  is run by tire community,  the ritual  Kungkum  and  Pepe.  Kw1gkum  is a  ritual that  requires male members of this community  to soak at a time or flow from 11ight until  morning for four months.  Similarly, the ritual Pepe is a ritual  with a physical  body drying under the s1111. The whole ritual is executed with tire  meaning that  as  a human being  should  train themseloes to rid yourself of the body, mind, heart and passion of the world and as ,m attempt   to  overcome  the temptations that often occur  in  man, both physically  and me11tally as well as an attempt  to blend with the natural which luts  berm widely credited for humans.